2012
DOI: 10.1007/s13730-012-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

A distinct lymphocyte distribution in relapse after rituximab for steroid-dependent nephrotic syndrome

Abstract: Rituximab (RTX) is a new steroid-sparing therapy for childhood steroid-dependent nephrotic syndrome (NS). However, relapses frequently occur immediately after CD19 recovery. We report the cases of two steroid-dependent NS patients treated with RTX followed by mizoribine (MZB). One patient relapsed, and the other developed proteinuria after CD19 recovery until the MZB was replaced by mycophenolate mofetil. These patients exhibited different lymphocyte phenotypes, with the CD4?/CD8? profile favoring CD8? T lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The pathophysiology of INS remains unclear; however, abnormal T cell function and humoral factors from T cells play a crucial role in INS . The expansion of CD3 + HLA‐DR + ‐activated T cells was observed in patients with INS . A recent report showed that the percentage of CD3 + CD4 + HLA‐DR + T cells were lower in FSGS patients who responded to RTX than in those who did not respond to RTX .…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of INS remains unclear; however, abnormal T cell function and humoral factors from T cells play a crucial role in INS . The expansion of CD3 + HLA‐DR + ‐activated T cells was observed in patients with INS . A recent report showed that the percentage of CD3 + CD4 + HLA‐DR + T cells were lower in FSGS patients who responded to RTX than in those who did not respond to RTX .…”
Section: Discussionmentioning
confidence: 99%